Diversity and dissent : negotiating religious differences in Central Europe, 1500-1800 - Louthan, Howard, 1963-; Cohen, Gary B.; Szabo, Franz A. J. (Austrian and Habsburg studies ;, 2011)
Early modern Central Europe was the continent's most decentralized region politically and its most diverse ethnically and culturally. With the onset of the Reformation, it also became Europe's most religiously divided territory and potentially its most explosive in terms of confessional conflict and war. Focusing on the Holy Roman Empire and the Polish-Lithuanian Commonwealth, this volume examines the tremendous challenge of managing confessional diversity in Central Europe between 1500 and 1800. Addressing issues of tolerance, intolerance, and ecumenism, each chapter explores a facet of the complex dynamic between the state and the region's Catholic, Protestant, Orthodox, Utraquist, and Jewish communities. The development of religious toleration-one of the most debated questions of the early modern period-is examined here afresh, with careful consideration of the factors and conditions that led to both confessional concord and religious violence.